Consumer cross-channel behaviour: is it always planned?. Issue 12 (5th August 2020) - Maggioni, Isabella; Sands, Sean James; Ferraro, Carla Renee; Pallant, Jason Ian; Pallant, Jessica Leigh; Shedd, Lois; Tojib, Dewi
Abstract : Purpose: For consumers, cross-channel behaviour is increasingly prevalent. Such behaviour involves consumers actively engaging in (and deriving benefit) from one channel during a product search but switching to another channel when making a purchase. Drawing on multi-attribute utility theory, this study proposes a cross-channel behaviour typology consisting of three key aspects: channel choice behaviour, functional and economic outcomes and consumer-specific psychographic and demographic variables. Design/methodology/approach: Segmentation analysis conducted via latent class analysis (LCA) was performed on a sample of 400 US consumers collected via an online survey. Findings: Cross-channel behaviour is not always intentional. We identify a specific segment of consumers that most often engage in unplanned, rather than intentional, cross-channel switching. We find that of all shoppers that engage in cross-channel behaviour, a fifth (20%) are forced to switch channels at the point of purchase. Practical implications: Cross-channel behaviour can be mitigated by retailers via a deep understanding of the driving factors of different configurations of showrooming and webrooming. Originality/value: In contrast with existing conceptualisations, this study suggests that cross-channel behaviour often stems from consumers being "forced" by factors outside of their control, but within the retailers' control. This research presents a nuanced approach to decompose consumer cross-channel behaviour from the consumer perspective as planned, forced or opportunistic.